Highly potent artemisinin-derived dimers and trimers: Synthesis and evaluation of their antimalarial, antileukemia and antiviral activities. Issue 17 (1st September 2015) - Reiter, Christoph; Fröhlich, Tony; Gruber, Lisa; Hutterer, Corina; Marschall, Manfred; Voigtländer, Cornelia; Friedrich, Oliver; Kappes, Barbara; Efferth, Thomas; Tsogoeva, Svetlana B.
Graphical abstract: Abstract: New pharmaceutically active compounds can be obtained by modification of existing drugs to access more effective agents in the wake of drug resistance amongst others. To achieve this goal the concept of hybridization was established during the last decade. We employed this concept by coupling two artemisinin-derived precursors to obtain dimers or trimers with increased in vitro activity against Plasmodium falciparum 3D7 strain, leukemia cells (CCRF-CEM and multidrug-resistant subline CEM/ADR5000) and human cytomegalovirus (HCMV). Dimer4 (IC50 of 2.6 nM) possess superior antimalarial activity compared with its parent compound artesunic acid (3 ) (IC50 of 9.0 nM). Dimer 5 and trimers 6 and7 display superior potency against both leukemia cell lines (IC50 up to 0.002 μM for CCRF-CEM and IC50 up to 0.20 μM for CEM/ADR5000) and are even more active than clinically used doxorubicin (IC50 1.61 μM for CEM/ADR5000). With respect to anti-HCMV activity, trimer 6 is the most efficient hybrid (IC50 0.04 μM) outperforming ganciclovir (IC50 2.6 μM), dihydroartemisinin (IC50 >10 μM) and artesunic acid (IC50 3.8 μM).